Effects of lycopene on high glucose-induced autophagy and apoptosis of podocytes - LI Ni; YANG Xiang-li; HUANG Qiao; JIA Lin; LIU Chang-xuan; LI Yong-xia; CHEN Wen-li (Linchuang shenzangbing zazhi)
Objective To investigate the effects of lycopene( Lyc) on high glucose-induced autophagy and apoptosis of podocytes in order to provide a reliable theoretical basis for the clinical treatment of diabetic nephropathy. Methods The immortalized mouse podocyte line was used as the study subjects,and the high glucose-induced podocytes were intervened by the addition of different doses of lycopene.The experimental cells were divided into 6 groups: control group( 5. 5 mmol/L glucose),hyperosmolar group( 5. 5 mmol/L glucose + 19. 5 mmol/L mannitol),high glucose group( 25 mmol/L glucose),high glucose + low dose Lyc group( 25 mmol/L glucose + 3. 125 μmol/L Lyc),high glucose+ middle dose Lyc group( 25 mmol/L glucose + 6. 25 μmol/L Lyc) and high glucose + high dose Lyc group( 25 mmol/L glucose + 12. 5 μmol/L Lyc). After culture for 48 h,the autophagic changes of the cells were observed by acridine orange staining. The flow cytometry was used to detect the apoptosis rateof each group,and the expression levels of LC3-II,beclin-1,p62/SQSTMI mRNA and protein were detected by Real-Time PCR and Western blotting,respectively. Results The number of autophagosomes in the high glucose group was significantly greater than that in the normal glucose group and high permeability group. The apoptosis rate of the cells in high glucose group was significantly higher( P < 0. 01).The expression of autophagy-related genes LC3-II and beclin-1 was significantly increased( P < 0. 05),while that of p62/SQSTMI gene was significantly decreased( P < 0. 05). As compared with the high glucose group,the number of autophagosomes in different doses of lycopene group was significantly increased;the apoptosis rate of the cells was significantly reduced( P < 0. 05),and the apoptosis rate of the cells in high glucose + high dose lycopene group was extremely significantly decreased( P < 0. 01).The expression of autophagy-related genes LC3-II and beclin-1 was significantly increased( P < 0. 05).The expression of p62/SQSTMI gene was significantly reduced( P < 0. 05),and that in high glucose +high dose lycopene group was decreased extremely significantly( P < 0. 01). The results of Western blotting on the protein level were consistent with those of RT-PCR. Conclusions Lycopene can further enhance the autophagy of podocytes induced by high glucose,but it still inhibits the apoptosis of podocytes,and the effect of high-dose lycopene is more obvious.